Advances and perspectives in genetic expression and operation for the oleaginous yeast Yarrowia lipolytica - Mengchen Hu; Jianyue Ge; Yaru Jiang; Xiaoman Sun; Dongshen Guo; Yang Gu (Synthetic and Systems Biotechnology)
The utilization of industrial biomanufacturing has emerged as a viable and sustainable alternative to fossil-based resources for producing functional chemicals. Moreover, advancements in synthetic biology have created new opportunities for the development of innovative cell factories. Notably, Yarrowia lipolytica, an oleaginous yeast that is generally regarded as safe, possesses several advantageous characteristics, including the ability to utilize inexpensive renewable carbon sources, well-established genetic backgrounds, and mature genetic manipulation methods. Consequently, there is increasing interest in manipulating the metabolism of this yeast to enhance its potential as a biomanufacturing platform. Here, we reviewed the latest developments in genetic expression strategies and manipulation tools related to Y. lipolytica, particularly focusing on gene expression, chromosomal operation, CRISPR-based tool, and dynamic biosensors. The purpose of this review is to serve as a valuable reference for those interested in the development of a Y. lipolytica microbial factory.